Advances in glycopeptide enrichment methods for the analysis of protein glycosylation over the past decade. Issue 16 (18th July 2022) - Li, Jiajia; Zhang, Jie; Xu, Mingming; Yang, Zeren; Yue, Shuang; Zhou, Wanlong; Gui, Chunshan; Zhang, Haiyang; Li, Shuwei; Wang, Perry G.; Yang, Shuang
Abstract : Advances in bioanalytical technology have accelerated the analysis of complex protein glycosylation, which is beneficial to understand glycosylation in drug discovery and disease diagnosis. Due to its biological uniqueness in the course of disease occurrence and development, disease‐specific glycosylation requires quantitative characterization of protein glycosylation. We provide a comprehensive review of recent advances in glycosylation analysis, including workflows for glycoprotein digestion, glycopeptide separation and enrichment, and mass spectrometry sequencing. We specifically focus on different strategies for glycopeptide enrichment through physical interaction, chemical oxidation, or metabolic labeling of intact glycopeptides. Recent advances and challenges of O‐glycosylation analysis are presented, and the development of improved enrichment methods combining different proteases to analyze O‐glycosylation is also proposed.